Evaluation of Blood Sugar Levels in Diabetes Mellitus Patients with Gangrene Complications in Hospital at Palu City - Ingrid Faustine (Journal of Global Pharma Technology, 2020)
From year to year, the amounts of gangrene patients continue to gradually increase. This is due to lack of consistent routines in checking blood sugar levels which result in blood sugar levels being uncontrolled. In gangrene patients who do not receive treatments, this will lead to amputation and can reduce the patient's quality of living. This study aims to determine the blood sugar levels in patients with diabetes mellitus with gangrene complications in hospitals in Palu City. The method used in the study is cross-sectional with prospective data collection, in which for examination of GDP is implemented using the auto check tool. The results of this study utilized the wilcoxon test to see a decrease in blood glucose levels before and after receiving antidiabetic and insulin therapy. The total research samples consisted of 30 patients within 1 month monitoring duration. From the results of research conducted for 3 months, it showed a significant decrease in fasting patients' blood glucose levels, with an average value before and after using antidiabetic therapy indicated as 285.87 mg / dl and 173.07 mg / dl. It is then concluded that there is a decrease in blood sugar levels in patients who suffer from diabetes mellitus with gangrene complications due to the use of antidiabetic therapy, namely insulin.Keywords: Blood Sugar Levels; Diabetes Mellitus; Gangrene; Insulin.